PLANNING ENGLISH LANGUAGE CLASSES FROM THE CRITICAL LITERACY PERSPECTIVE: FOCUSING ON RACISM AND SOCIAL ISSUES - Silva, Nayara Stefanie Mandarino (Revista X, 2020)
Considering that English language teaching in public schools requires forming critical citizens (JUCÁ, 2016), this study addresses the work with critical literacy in classrooms. Therefore, my aim is to analyze the process of planning English language classes from the critical literacy perspective (MENEZES DE SOUZA, 2011a; 2011b), focusing on racism and social issues. The three classes lead to writing a personal report, using can, considering the social, historical and political barriers people may face depending on their position within specific time and space.